Some aspects of irrigation systems performance in Palestine - Nofal I.; Dudeen B.; Rabi A. (Irrigation systems performance, 2005)
In this paper are presented the main aspects of irrigation systems in Palestine including also the data related to the availability of water resources, distribution of irrigable and irrigated lands and agricultural water demand projections. In year 2000, agricultural water demand was about 190 million cubic meters of water necessary for irrigation of about 22,000 hectares. It is estimated that for each one million of people there is a need to irrigate additional 7,500 hectares which will require about 61 million cubic meters of water each year. There is a consensus that a significant amount of water could be saved through rehabilitation of water infrastructure (wells, springs, ponds, etc.) increasing the efficiency of water delivery and irrigation systems and intensifying and strengthen extension and research activities and the transfer of technology. A particular attention should be given to the substitution of open earthen or lined canals with the closed conduits delivery network which could contribute to the reduction of losses up to 25 percent.
2. WASAMED Workshop: Irrigation Systems Performance, 2004/06/24-28, Hammamet (Tunisia)